Ischaemia-reperfusion time differences in ST-elevation myocardial infarction in very young patients: a cohort study - Pablo Juan-Salvadores; Luis Mariano De La Torre Fonseca; Beatriz Calderon-Cruz; Cesar Veiga; Samuel Pintos-Rodríguez; Saleta Fernandez Barbeira; Victor Alfonso Jimenez Diaz; Andres Iñiguez Romo (Open Heart)
Introduction ST-elevation myocardial infarction (STEMI) is one of the most prevalent presentations in young patients. It is essential to emphasise that each minute of delay in providing medical care is negatively correlated to the patient’s prognosis. The present study was carried out to evaluate the ischaemia-reperfusion times in patients ≤40 years of age versus individuals >40 years of age and their association with mortality and major adverse cardiac event (MACE) over the long term.Methods A retrospective, multicentre cohort study was carried out in 6799 patients diagnosed with STEMI. Two groups were established: patients diagnosed with STEMI and aged >40 years, and patients diagnosed with STEMI and aged ≤40 years.Results The patients in the young group had a significantly sooner electrocardiographic diagnosis than the patients >40 years of age. A delay was observed in females, with a relative risk (RR) of 1.21 (95% CI 1.13 to 1.30) (p<0.001). Presenting dyspnoea (RR 1.76, 95% CI 1.5 to 2.06) (p<0.001) or going to a hospital without haemodynamics (RR 1.55, 95% CI 1.45 to 1.67) (p<0.001) was related to increased delay. The occurrence of MACE in the first year of follow-up was related to different risk factors, along with a delay in healthcare (HR 1.25, 95% CI 1.10 to 1.54) (p<0.042).Conclusion This study shows that young patients with STEMI tend to receive a sooner diagnosis than older individuals. Delays in healthcare represent one of the main factors related to the occurrence of MACE and non-event-free survival.